An Agile Management Model for Distributed Software Development Teams - Montalvão Junior, David; Batista, Thais; Cavalcante, Everton (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2023: Anais do XXXVII Simpósio Brasileiro de Engenharia de Software, 2023)
Agile project management models are notorious in current software development. However, distributed teams pose management challenges, such as the need for effective communication and collaboration tools and the difficulty of monitoring progress and work quality. This paper presents the Agile Management Model for Distributed Software Development Teams (AgiTeD), a Scrum-inspired framework grounded on transparency, inspection, adaptation, and quality. AgiTeD defines four roles, six events within the development cycle, and seven artifacts. We applied the proposed model to a distributed team and surveyed 23 developers working remotely on eight different projects of an organization. The developers highlighted some positive facets of AgiTeD for better supporting the work of distributed software development teams, emphasizing the Agile Leader role to ensure the full implementation of the model, the proposed cycle and its events, and the Repository and Communication Rules artifact to organize the teamwork.